2016
DOI: 10.1111/jfpp.12753
|View full text |Cite
|
Sign up to set email alerts
|

Determinative Effects of Fat Replacement and Homogenization on the Sensory and Rheological Properties of Low-Fat Mozzarella

Abstract: Low-fat Mozzarella with 6% fat was produced by using fat replacers at three levels of protein concentrations including 35% (Dairy-Lo), 53% (Simpless) and 90% (LSI907). The effects of fat substitution and cream homogenization on rheological and sensory properties of cheese were investigated after 1, 7, 14 and 28 days of storage at 4C. Data showed that meltability and stretchability increased on 14th day, then reduced while hardness decreased on 28th day of storage. It was quite obvious that the lowest moisture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Numerous techniques are employed to boost textural and flavour anomalies of LF cheese, and one of the most promising is the use of fat replacers. The use of three whey protein‐based fat replacers (Dairy‐Lo) (purity indices 35%), Simpless (53% sincerity) and LS1907 (90% purity indices) was reported for the successful preparation of the LF mozzarella cheese (Tahereh et al ., 2017). In food processing industries, plant and microbial gums including alginate, guar gum, carrageenan, maltodextrins, pectin, mucilage and xanthan gum are widely used as polysaccharides stabilisers to restrict water mobility and impart fatty mouthfeel (Aziz et al ., 2018; Dantas et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous techniques are employed to boost textural and flavour anomalies of LF cheese, and one of the most promising is the use of fat replacers. The use of three whey protein‐based fat replacers (Dairy‐Lo) (purity indices 35%), Simpless (53% sincerity) and LS1907 (90% purity indices) was reported for the successful preparation of the LF mozzarella cheese (Tahereh et al ., 2017). In food processing industries, plant and microbial gums including alginate, guar gum, carrageenan, maltodextrins, pectin, mucilage and xanthan gum are widely used as polysaccharides stabilisers to restrict water mobility and impart fatty mouthfeel (Aziz et al ., 2018; Dantas et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the studies so far (Deegan et al, 2013;Karaman and Akalın, 2013;Logan et al, 2015;O'Mahony et al, 2005) have reported on the effect of size of MFGs and homogenization on reduced fat and full fat cheeses only. Other studies (Karaman et al, 2012;Nair et al, 2000;Tahereh et al, 2017;Van Hekken et al, 2007) suggested homogenization as one of the modifying techniques to improve the textural and other characteristics of low fat cheeses, but did not study the effect of emulsion size. Incorporation of milk fat emulsions in micron to nanosize range as a texture modifier in low-fat Cheddar cheese has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%